Tetrandrine inhibits colon carcinoma HT-29 cells growth via the Bcl-2/Caspase 3/PARP pathway and G1/S phase. Issue 5 (14th May 2019) - Li, JiaNan; Wang, QiuHong; Wang, ZhiBin; Cui, Na; Yang, BingYou; Niu, WenYing; Kuang, HaiXue
Abstract : Tetrandrine (Tet) bisbenzylisoquinoline alkaloids isolated from Stephania tetrandra and other related species of Menispermaceae. It has been demonstrated to have positive therapeutic effects on cardiovascular disease, hypertension, silicosis, autoimmune diseases. In recent years, some reports have shown that Tet has anticancer activity in human cancers. To explore the pharmacological activity and mechanism of Tet on colon cancer and its unique advantages as a natural product. In the present study, analyses of the cell cycle, apoptosis, targets prediction, molecular docking, and alterations in protein levels were performed to elucidate how Tet functions in colon cancer. We found that Tet robustly induced arrest at the G1 phase in colon cancer cell line HT-29. It induced HT-29 cell apoptosis in a dose-dependent manner. Similarly, analysis of protein expression levels in HT-29 cells showed down-regulation of Bcl-2, pro-caspase 3, pro-caspase 8, PARP, cyclin D1 (CCND1), cyclin-dependent kinase 4 (CDK 4), and up-regulation of Bax, active caspase 3, and active caspase 8. These results indicate that Tet induces apoptosis of colon cancer cells through the mitochondrial pathway and caspase family pathway. Molecular docking showed interaction effects and binding energy. Comparing with the CDK4 inhibitors ribociclib and palbociclib, the docking energy is similar to the docked amino acid residues. Therefore, we conclude that Tet and the CCND1/CDK4 compound could form hydrogen bonds and a stable compound structure, which can inhibit colon cancer cells proliferation by regulating CCND1/CDK4 compound and its downstream proteins phosphorylated Rb (p-Rb). In summary, Tet may be a potential drug for colon cancer therapy.